Récit de voyage et écriture engagée : Jean de Léry au service des Coligny - Alexandre Tarrête (Viatica)
Jean de Léry wrote the Histoire d’un voyage faict en la terre du Brésil (1578) when he was staying at François de Coligny’s mansion, in Berne. Describing the marvels of America from a scientific point of view, his book has also a political purpose: praising the memory of late admiral Gaspard of Coligny, who sent the first french expedition to Brazil, in order to challenge the Portuguese and Spanish ambitions in South America, as well as to announce the Gospel to the Savage. The polemic between Léry and Thevet also reflects the political rivalry between the Guise and the Coligny family.